THE EFFECTIVENESS OF HEALTH LITERACY PROGRAM FOR NEW RISK STUDENT GROUP TO PREVENTIVE ALCOHOL DRINKING BEHAVIORS IN OPPORTUNITY EXPANSION SCHOOL PAK THONG CHAI DISTRICT NAKHON RATCHASIMA PROVINCE - พิมพ์จันทร์ ศิริวรรณ; เพชรมณี สาโรจน์; ปัญญาใสโสภณ ธณกร (Primary Health Care Journal (Northeastern Edition), 2024)
The quasi-experimental study aimed to investigate the effectiveness of a health knowledge program for students at risk of alcohol consumption in a school in Pak Thong Chai District, Nakhon Ratchasima Province. The sample comprised two groups: an experimental group of 30 students who received the health knowledge program and a control group of 30 students who received regular programming. Simple random sampling was employed. The research utilized a health knowledge program to measure health knowledge and alcohol consumption prevention behaviors. Statistical analyses included frequency, percentage, mean, standard deviation, and t-tests (paired and independent samples). The study found that after the intervention, the experimental group demonstrated significantly higher levels of knowledge, understanding, access to health information, communication proficiency, self-management, media literacy, decision-making skills, and alcohol consumption prevention behaviors compared to both their baseline and the control group, with statistical significance at the .01 level.